Exploring Social and Solidarity Economy (SSE) during the Greek Economic Crisis - Papadaki, Marina; Kalogeraki, Stefania (PARTECIPAZIONE E CONFLITTO, 2018)
In the last decades, Social and Solidarity Economy (SSE) has become an everyday practice for an increasing number of citizens, and the SSE sector has been constantly expanding. Particularly, during hard economic times, SSE has acted as a viable economic alternative and as a means to support vulnerable social groups, hit by the recession. However, SSE does not merely act as an emergency actor during harsh economic times, but also as a form of resistance to neoliberal dominance and as a tool of empowerment, transformation and social change. This paper, using quantitative data from the LIVEWHAT project, ex-plores SSE organisations in Greece, as one of the European countries most severely affected during the recent global financial crisis. The results, which are indicative of the Greek SSE sector during the period under study, shed light on the role of the recession as one of the main triggers for the recent expansion of SSE organisations that are often less formally organised, and primarily act as coping mechanisms, which aim to meet the uncovered, urgent socioeconomic needs of citizens. The findings also demonstrate that the Greek SSE sector, under study, acts as an economic alternative, promoting collective action and new social movements.